2015
DOI: 10.1016/j.jvir.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Percutaneous Biliary Interventions for Biliary Anastomotic Stricture in Pediatric Patients after Living Donor Liver Transplantation with Roux-en-Y Hepaticojejunostomy

Abstract: PTBD followed by balloon dilation and internal drainage may be an effective treatment for anastomotic biliary stricture after pediatric LDLT with RYHJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The conclusive cure rate with IVR treatment in hepatic vein complications was 84.2%, in portal vein complications was 97.4%, in hepatic artery complications was 100%, and in biliary complications was 88.0% (Table ). Furthermore, it has been reported that the cure rate from IVR treatment for hepatic vein, portal vein, and biliary complications was greater than 85% (Table ) . In addition, in the present study, the graft survival rates in patients with and without post‐transplant vascular and biliary complications were 94.4% and 90.6%, respectively ( P = 0.522).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The conclusive cure rate with IVR treatment in hepatic vein complications was 84.2%, in portal vein complications was 97.4%, in hepatic artery complications was 100%, and in biliary complications was 88.0% (Table ). Furthermore, it has been reported that the cure rate from IVR treatment for hepatic vein, portal vein, and biliary complications was greater than 85% (Table ) . In addition, in the present study, the graft survival rates in patients with and without post‐transplant vascular and biliary complications were 94.4% and 90.6%, respectively ( P = 0.522).…”
Section: Discussionsupporting
confidence: 48%
“…In recent years, with advances in endovascular and endoscopic instruments and techniques, reports of novel endovascular and endoscopic treatments for vascular and biliary complications have increased. Therefore, endovascular and endoscopic interventions may become the first‐line treatment, even in pediatric recipients .…”
Section: Discussionmentioning
confidence: 99%
“…In our reported study [22] , clinical success, tube independent rate, and patency rate were evaluated. Clinical success is defined as resolution or marked improvement of clinical symptoms including fever, and improvement of laboratory findings, including the serum levels of AST, ALT, total bilirubin, direct bilirubin, r-GTP, and ALP.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, long-term PTBD is commonly accepted in the treatment of benign biliary strictures which are unable to be managed with endoscopic approach, especially in patients with bile duct stricture following liver transplantation. 12 As our patient underwent Roux-en-Y choledochojejunostomy and cholecystectomy due to severe inflammation and adhesion with suspicion for malignancy, the optimal treatment of postoperative biliary stricture at the anastomosis site was a percutaneous approach.…”
Section: Casementioning
confidence: 99%